Detection of human case of dengue virus 2 belonging to sylvatic genotype during routine surveillance of fever in Senegal, Kolda 2021 - Dieng, Idrissa; Sagne, Samba Niang; Ndiaye, Mignane; Barry, Mamadou Aliou; Talla, Cheikh; Mhamadi, Moufid; Balde, Diamilatou; Toure, Cheikh Talibouya; Diop, Boly; Sall, Amadou Alpha; Fall, Gamou; Loucoubar, Cheikh; et al. (Frontiers in Virology, 2022)
Dengue virus 2 (DENV-2) was detected in a febrile patient living in Saré Yoba in the Kolda region of southern Senegal. Phylogenetic analysis based on the full coding region revealed that the virus belongs to the DENV-2 sylvatic genotype and is closely related to a strain (JF260983/99.66% identity) detected in Spain in a tourist who traveled to Guinea-Bissau (which borders the Kolda region) in 2009. This highlights a potential recent under-reported circulation of sylvatic dengue in the southern part of Senegal and calls for reinforced integrated surveillance among humans, non-human primates, and arboreal mosquitoes through a one-health approach.